Economics of attention: The gender-based bing communication study on depression. (March 2022) - Hswen, Yulin; Ulrich, Nguemdjo; Elad, Yom-Tom; Bruno, Ventelou
Abstract: This study examines the impact of personalized gender-based communication to encourage the screening of depression and seeking out mental health care consultation. An internet search engine advertisement was deployed on Bing, Microsoft during the COVID-19 pandemic lockdowns in the Provence–Alpes–Côte d'Azur (PACA) region in France during the month of May 2020, the height of the France lockdowns. A two-armed study was conducted with Arm A containing a non-personalized (control) advertisement and Arm B containing a personalized gender-based advertisement. 53, 185 advertisements were shown between the two arms. Results show that receiving a personalized gender-based message increases the probability of clicking on the advertisement. However, upon clicking the advertisement, there was no significant difference in the completion of the depression questionnaire between the two groups. These results suggest that although personalized gender messaging is effective at drawing in a greater click rate, it did not increase, nor decreased, the conversion rate to monitor depression by self-assessment. Highlights: Personalized gender-based messages increase the click-rate probability on an advertisement for self-screening of depression. Personalized gender-based messages did not increase/decrease the conversion rate to intend to seek medical help for depression. Youth under the age of 25 who were considered depressed were less likely to have the intent to seek future treatment.